(untitled) (Journal of Enam Medical College, 2024)
Background: Surface epithelial tumor is the most common type of ovarian tumor making up 65% of all ovarian neoplasms. The proliferative activity of tumor can be estimated by many methods and the analysis of silver binding nucleolar organizer region (AgNOR) is one of them. Two types of AgNOR counts were calculated – mAgNOR and pAgNOR. Objective: To find out expression of AgNOR staining in benign, borderline and malignant epithelial tumors of ovary and its correlation with tumor grading. Materials and Methods: This cross-sectional study was conducted in the department of Pathology, Sir Salimullah Medical College, Dhaka from March 2018 to July 2020. In this study 70 diagnosed cases of benign, borderline and malignant epithelial tumors of ovary were enrolled. Corresponding paraffin blocks were collected. Ethical practice was ensured in every step of the study. Statistical analysis was carried out as required. Statistical significance was considered at <0.05. Results: Most of the patients were in 31−40 years age group. Most commonly observed epithelial tumors were benign in nature followed by malignant tumors and only two cases were borderline. The mean mAgNOR in malignant tumors was 3.62±0.57, with benign tumors was 1.68±0.53 and with borderline tumors was 1.65±0.21. Progressive increase in AgNOR expression was noted from benign to malignant epithelial ovarian tumors. The mean mAgNOR found in Grade I, Grade II and Grade III were 3.29±0.37, 3.76±0.59 and 4.33±0.15 respectively. Significant differences were found among the all groups and when compared between Grade I and Grade II, also between Grade I and Grade III. The mean pAgNOR found in Grade I, Grade II and Grade III were 13.54±3.05, 16.19±4.35 and 21.33±1.15 respectively. Significant differences were found among the groups and also when compared between Grade I and Grade III. There was significant positive correlation between histological grading of ovarian tumor with mAgNOR (r=0.589; p=0.001) and with pAgNOR (r=0.510; p=0.003). Conclusion: mAgNOR and pAgNOR expressions were significantly elevated in malignant tumors compared to benign and borderline tumors. mAgNOR and pAgNOR are useful markers of cellular kinetics and good prognostic factors in epithelial tumors of ovary. J Enam Med Col 2022; 12(1): 29−35